Healthy dietary practices and its’ associated factors among adults of Nekemte dwellers, Oromia State, Western Ethiopia - Adeba, Alemu; Tamiru, Dessalegn; Belachew, Tefera (Frontiers in Nutrition, 2024)
Background and purposes Appropriate healthy dietary practices are essential for well-being. Adopting of healthy lifestyle remains challenging worldwide. Ethiopia has an unacceptably high burden of malnutrition like other least developed countries. However, healthy dietary practices and their associated factors were not conducted in Nekemte town. Hence, the study was designed to assess healthy dietary practices and associated factors among middle-aged adults in Nekemte town from January 15 to February 30, 2019. Methods A community-based cross-sectional study design was applied in Nekemte town. Primary data were gathered using a questionnaire from 266 adults and checked for normality. In both bivariate and multivariate logistic regression analyses the association and significance were determined at P < 0.05. Results The Magnitude of dieting practice was 73.31% (unhealthy) and 26.69% (healthy), respectively. Being low-income households (P = 0.001), not married (p = 0.001), had a daily meal frequency [AOR: 1.91, 95% CI: (1.04, 2.71), and had poor knowledge of healthy diet AOR: 3.87, 95% CI: (3.23, 5.65)] were associated with unhealthy diets. Conclusion The researchers identified unhealthy diet practices were widespread in the study samples of Nekemte populations. Hereafter, community-based lifestyle and Nutrition education through intensive participation of community leaders is highly recommended.